Sistem Informasi Geografis Sebaran Lembaga Pendidikan Qur’an (LPQ) Menggunakan Algoritma A-Star - Khairani Maudi Pangestu; Suendri; Muhamad Alda (STMIK Budi Darma, 2023)
The development of Lembaga Pendidikan Qur’an (LPQ) in Medan City is currently expanding, but in obtaining information about Lembaga Pendidikan Qur’an in Medan City is still minimal. Due to the absence of technology-based media used to display location points and routes to LPQ in Medan City. The purpose of this study is to build a geographic information system that can display location point information, the closest route and other information related to LPQ. By using the Research and development research method which aims to create or develop a new product, and implement the A-Star algorithm in order to find the closest route to that location. While in developing the system, the author uses the Rapid Application Development method where at this stage the system built by the author is then tested blackbox testing to find out whether every process in the system is in accordance with its function or not. The final result in this study is a geographic information system application for mapping the distribution of the Lembaga Pendidikan Qur’an (LPQ) based on Android that can be used by the community, especially for those who have children and want to participate in learning activities at Lembaga Pendidikan Qur’an